Copper Oxide Nanoparticles suppress the liver and kidney function and decrease antioxidant defense in adult male rats after acute oral administration - Rehab Mohamed; Ibrahem M. A. Hasan; Zainab M. Maher; Hassan Ahmed (SVU-International Journal of Veterinary Sciences, 2023)
Copper oxide nanoparticles (CuO NPs) were green synthesized using the aqueous extract of banana peels. CuO NPs were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) surface area analysis. Analyses confirmed the formation of crystalline CuO with 15 nm particle size and 9 m2g-1 surface area. The current study is an endeavor to explore the in vivo impact of acute different oral doses of the synthesized CuO NPs. One hundred and fifty adult male albino rats were used, they divided into 5 groups, each group contained 3 replicates (n = 30). Rats were administered suspension of CuO NPs using oral gavage in different concentrations (0, 100, 200,1000, and 2000 mg/kg) as a single dose. Liver and kidney function markers (AST, ALP, ALP, urea and creatinine) as well as antioxidant enzymes (catalase and glutathione reductase) were evaluated 2, 8 and 15 days after administration. The results revealed a high mortality rate with rats receiving 1000 and 2000 mg/kg (16% and 30.7%, respectively). Further, within the same high doses, rats showed marked elevation of serum AST, ALP, ALP, urea and creatinine after 2, 8 and 15 days from administration. However, the activity of catalase enzyme declined significantly at the same timepoints with the former high doses. Moreover, the activity of glutathione reductase enzyme in the liver homogenate showed marked decrease after administration of all CuO NPs doses. In conclusion, the harmful effect of CuO NPs appears with the higher dose so, attention should be considered during use of CuO NPs as nutritive supplements.